Pregnant women carrying female fetuses are at higher risk of placental malaria infection - Adam, Ishag (PLoS One, 2017)
BACKGROUND: The pathophysiology of the placental malaria is not fully understood. If there is a fetal sex–specific susceptibility to malaria infection, this might add to the previous knowledge on the immunology, endocrinology and pathophysiology of placental malaria infections. AIMS: This study was conducted to assess whether the sex of the fetus was associated with placental malaria infections. SUBJECTS AND METHODS: A cross-sectional study was performed including a secondary analysis of a cohort of women who were investigated for prevalence and risk factors (including fetal sex) for placental malaria in eastern Sudan. Placental histology was used to diagnose placental malaria infections. RESULTS: Among 339 women enrolled, the mean (SD) age was 25.8 (6.7) years and parity was 2.7 (2.2). Among the new born babies, 157 (46.3%) were male and 182 (53.7%) were female. Five (1.5%), 9 (2.7%) and 103 (30.4%) of the 339 placentas had active, active-chronic, past-chronic malaria infection on histopathology examination respectively, while 222 (65.5%) of them showed no malaria infection. Logistic regression analyses showed no associations between maternal age or parity and placental malaria infections. Women who have blood group O (OR = 1.95, 95% CI = 1.19–3.10; P = 0.007) and women who had female new born were at higher risk for placental malaria infections (OR = 2.55, 95% CI = 1.57–4.13; P< 0.001). CONCLUSION: Fetal gender may be a novel risk factor for placental malaria. In this work the female placentas were at higher risk for malaria infections than the male placentas.